Microencapsulation of Cassia Alata: fabrication and characterization - Alfatama, Mulham; Ahmad, Kausar; Mohamed, Farahidah (Academic Sciences, 2012)
Senna alata or Cassia alata (C. alata) is a plant belonging to the family Leguminosae and has been documented to have antifungal and antimicrobial activities. This research aims to extract C. alata, followed by microencapsulation by solvent-evaporation using biodegradable PLGA. The microsphere is envisaged to release the extract in a controlled manner allowing more convenient mode of administration when treating related skin infection. Several variables had been investigated including different types of surfactants and buffer systems and different homogenization times for primary emulsion. It was found that, most of the surfactants employed resulted in low encapsulation efficiency (<10%). However with 3% poly vinyl alcohol (PVA), slightly higher encapsulation efficiency of 11% was achieved, with size distribution of 7-13 μm. The encapsulation efficiencies were significantly improved (45-64.4%) when the hardening tank was buffered to pH 7, with minimal effect on particle size. Additionally, in-vitro controlled release formulation of C. alata microsphere was demonstrated for duration of almost a month.